2013
DOI: 10.3389/fnins.2013.00233
|View full text |Cite
|
Sign up to set email alerts
|

The role of the striatum in social behavior

Abstract: Where and how does the brain code reward during social behavior? Almost all elements of the brain's reward circuit are modulated during social behavior. The striatum in particular is activated by rewards in social situations. However, its role in social behavior is still poorly understood. Here, we attempt to review its participation in social behaviors of different species ranging from voles to humans. Human fMRI experiments show that the striatum is reliably active in relation to others' rewards, to reward i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
166
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(176 citation statements)
references
References 157 publications
(249 reference statements)
10
166
0
Order By: Relevance
“…For instance, learning that one has a good reputation among others, results significantly increased activity in the caudate and putamen (Izuma et al, 2008). Furthermore, fMRI studies demonstrate that the ventral striatum activates when participants decide to engage in prosocial behaviors, such as donating money to charity to help others (Báez-Mendoza and Schultz, 2013; Harbaugh et al, 2007; Moll et al, 2006). These studies reveal a causal relationship in which the social reward was experienced as a result of being liked or simply of producing a helping behavior, and this mechanistic understanding of the role of reward in prosocial behaviors is widely held (Fehr and Fischbacher, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, learning that one has a good reputation among others, results significantly increased activity in the caudate and putamen (Izuma et al, 2008). Furthermore, fMRI studies demonstrate that the ventral striatum activates when participants decide to engage in prosocial behaviors, such as donating money to charity to help others (Báez-Mendoza and Schultz, 2013; Harbaugh et al, 2007; Moll et al, 2006). These studies reveal a causal relationship in which the social reward was experienced as a result of being liked or simply of producing a helping behavior, and this mechanistic understanding of the role of reward in prosocial behaviors is widely held (Fehr and Fischbacher, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There is one study showing that impaired empathy (at least self-reported empathic abilities) in schizophrenia is associated with more severe negative symptoms (Konstantakopoulos et al, 2014), which might provide some evidence to relate psychotic symptoms to MNS function. More research has recently been emerging to confirm the rewarding nature of social interactions, as several neuroimaging studies have demonstrated the activation of reward centers during different types of social interaction, with many suggesting an integral role for reward processing in social learning processes (Báez-Mendoza & Schultz, 2013;Fareri, Niznikiewicz, Lee, & Delgado, 2012;Gariépy et al, 2014). If reward does play a role in social interaction and in promoting social goal-seeking and social motivation, then a deficit in reward processing is also likely to have a detrimental impact on social functioning and the acquisition of social skills.…”
mentioning
confidence: 99%
“…Evidence of a similar relationship between dopamine and reward uncertainty has also been reported in two human studies using fMRI [23,24]. This response to uncertainty has been used to explain our attraction to games of chance [25], although many other factors pertinent to playing video games, such as novelty [26] and social interaction [27], are also likely to play a role in determining midbrain DA release.…”
Section: Motivation Reinforcement Learning and Midbrain Dopaminementioning
confidence: 76%